V1: Targeting and Scaling Out - Barron, Jennie; Chadwick, Matthew; Cinderby, Steve; Kemp-Benedict, Eric (2010)
Numerous pilot studies and case studies in the Volta Basin have evaluated practices, methods, and tools that could prove beneficial to others, both within the basin and outside of it. However, the question whether an intervention successfully applied in one location has a reasonable chance of success at any other location remains extremely difficult to answer. A consistent finding in pilot studies is that detailed characteristics of the study location – economic, biophysical, institutional, and cultural – can all play an essential role in the eventual success, and failure of achieving a successful outcome. For out-scaling of initiatives it is impractical to collect detailed information at every potential site where an agricultural land and water management (AWM) intervention might be introduced. This project starts with the premise that, while certainty is unobtainable, degrees of certainty are both obtainable, using available information in a systematic way, and useful.The CPWF Project V1, “Targeting and Scaling Out”, proposal aims to develop an evidence and knowledge-based tool that will map the likelihood that a given intervention will be successful in given locations. The proposed V1 project will contribute to achieving the BDC challenge of improving rainwater and small reservoir management to contribute to poverty reduction and improved livelihoods resilience by producing a framework and web-based and electronic “decision support”, (or targeting and scaling out tool) that will identify likely sites to introduce AWM interventions for smallholder farming systems.